The impact of SARS-Cov-2 infection on the periocular injection pain and hypersensitive reaction to botulinum toxin type A: results from clinical questionnaires - Liu, Xiangyu; Tian, Yanli; Jiang, Chanyuan; Dong, Miao; Li, Ming; Sun, Hefeng; Han, Xuefeng; Li, Facheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The COVID-19 pandemic has brought about significant changes in the medical field, yet the use of botulinum toxin type A has remained uninterrupted. Plastic surgeons must carefully consider the timing of administering botulinum toxin type A to patients who have recovered from COVID-19. Methods: A questionnaire survey was conducted among patients who had contracted and recovered from SARS-CoV-2 within a month. The survey aimed to investigate various indicators in patients who had received botulinum toxin A injections at the same site before and after their infection, including pain scores and allergic reactions and the occurrence of complications. Results: The pain scores of patients who contracted SARS-CoV-2 infection between 14-21 days post-infection exhibited significant variation from previous injections. However, patients who contracted the infection between 22-28 days post-infection did not exhibit significant variation from previous injections. Furthermore, the incidence of allergic reactions and complications following botulinum toxin injection within one month after contracting the infection did not significantly differ from that observed prior to infection. Conclusion: Administering botulinum toxin type A three weeks after COVID-19 recovery is a justifiable and comparatively secure approach. Keywords: COVID-19, botulinum toxin, periocular wrinkles, hyperalgesia, allergic reaction